Complete chloroplast genome sequence and phylogenetic analysis of Magnolia pilocarpa, a highly ornamental species endemic in central China - Yu, Jiaojun (Mitochondrial DNA B Resour, 2020)
Magnolia pilocarpa Z. Z. Zhao et Z. W. Xie is a species with high horticultural and medicinal value, which found only in Dabie Mountain of central China. In this study, we sequenced, assembled and annotated the complete chloroplast (cp) genome of M. pilocarpa. The length of M. pilocarpa complete cp genome was 160,104 bp, with a typical quadripartite structure comprising a pair of inverted repeat regions (IRs; 26,591 bp), a large single copy region (LSC; 88,110 bp) and a small single copy region (SSC; 18,812 bp). The whole cp genome contained 129 unique genes, including 79 protein-coding genes (PCGs), 30 transfer RNA (tRNA) genes and four ribosomal RNA (rRNA) genes. The maximum-likelihood (ML) phylogenetic analysis indicated that M. pilocarpa was relatively closed to the M. denudata. This chloroplast genome would provide a valuable genetic resource for M. pilocarpa.